Improvement Antenna Performance by using Artificial Magnetic Conductor at 28 GHz - muhammad, maizatun; Abu, Maisarah; Zakaria, Zahriladha; hassan, hasnizom (Penerbit Universiti, UTeM, 2017)
The configurations of single patch antenna integrated with three different designs of patch artificial magnetic conductor (AMC) are presented in this paper in order to investigate the gain, radiation pattern, directivity and bandwidth of the antenna at a frequency of 28 GHz. Three cases of design configuration between patch antenna and three different designs of AMC are analyzed. First, configuration of patch antenna integrated with three designs of patch AMC. Second configuration of patch antenna integrated with non periodic patch AMC and third multilayer patch antenna with patch AMC. The details theory of the design configuration is explained. The simulated reflection coefficient and radiation pattern is presented. The simulated results showed that the gain, directivity and impedance bandwidth of all the design techniques are increased compared to patch antenna without AMC. For the first case, design of patch antenna integrated with design 1 AMC offer 13.96 % bandwidth and 12 % of the gain compared to patch antenna without AMC. In the second case, the overall size is reduced by 9.2 % and 14.14 % , respectively, compared with design in the first case. The third case of design structures provides more gain and bandwidth more than 3.57 %. In addition, the size is reduced compared to the previous two cases. Therefore, the result indicates the capability of this antenna integrated with AMC to be used for future 5G application. Index Terms: Artificial